2014
DOI: 10.5688/ajpe789162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Introductory Pharmacy Practice Experiences Among US Pharmacy Programs

Abstract: Objective. To identify the various IPPE designs utilized by US pharmacy programs. Methods. A 20-question survey was developed and distributed to experiential affairs professionals at 129 pharmacy institutions nationwide addressing school demographics and IPPE design. Results were analyzed in aggregate. Results. Ninety-three schools responded (72%). Eighty-nine percent of those reported beginning IPPE experiences in the first professional year, although there was a great variation regarding whether the IPPE was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In addition, 14 programs indicated that they did not have pathophysiology anywhere in their program, which could lead to underrepresentation if this was not an accurate reflection of their curriculum due to poorly written course descriptions. In our experience, 18,19 survey responses would not have resulted in as robust data due to the possibility of a poor response rate. Despite the fact that we had to exclude 8 programs, and 14 programs may have resulted in under representation, a poor survey response rate would have been more likely to skew our data by not having an adequate amount of programs to analyze.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, 14 programs indicated that they did not have pathophysiology anywhere in their program, which could lead to underrepresentation if this was not an accurate reflection of their curriculum due to poorly written course descriptions. In our experience, 18,19 survey responses would not have resulted in as robust data due to the possibility of a poor response rate. Despite the fact that we had to exclude 8 programs, and 14 programs may have resulted in under representation, a poor survey response rate would have been more likely to skew our data by not having an adequate amount of programs to analyze.…”
Section: Discussionmentioning
confidence: 94%
“…The first is that the study did not directly identify participants; rather it contacted the dean and asked them to forward the survey to the most appropriate student leader. This indirect contact may have hindered the response rate compared to what we previously received when directly contacting study participants 9 and could potentially have created nonresponder bias. However, the response rate and demographics were representative of the academy as a whole (in terms of class size and type of school), above 50% in every category (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…One respondent commented on the longitudinal nature of the IPPE at his or her institution, but block versus longitudinal IPPE opportunities were not specifically delineated in our survey. However, survey results reported by Galinski and colleagues 13 suggest at least some IPPEs are offered longitudinally at the majority of US pharmacy programs (69%). The authors feel utilization of a longitudinal IPPE experience may allow for greater student involvement in activities highlighted above, such as medication education groups.…”
Section: Discussionmentioning
confidence: 98%